2006
DOI: 10.1007/s00787-005-0522-3
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation, deliberate self-harm behaviour and suicide attempts among adolescent outpatients with depressive mood disorders and comorbid axis I disorders

Abstract: Depressed mood disorders, whether comorbid or not, are associated with suicidal ideation and suicide attempts. Diagnostic assessment should be supplemented by self-report methods when assessing suicidal behaviour in depressed adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 44 publications
4
42
0
4
Order By: Relevance
“…Moreover, despite differences in AIR-Y scores, there were no significant differences in risk for suicide between girls and boys. This is consistent with some prior work that has observed non-significant gender differences in adolescent suicidal behavior (e.g., Tuisku et al 2006), but inconsistent with the majority of evidence indicating girls, especially between ages 15 and 19 years, report higher rates of suicidal behaviors than boys, while boys are at greater risk for suicide (Nock et al 2008). Finally, the current sample lacked racial and ethnic diversity, and all participants self selected (and were compensated) to take part in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, despite differences in AIR-Y scores, there were no significant differences in risk for suicide between girls and boys. This is consistent with some prior work that has observed non-significant gender differences in adolescent suicidal behavior (e.g., Tuisku et al 2006), but inconsistent with the majority of evidence indicating girls, especially between ages 15 and 19 years, report higher rates of suicidal behaviors than boys, while boys are at greater risk for suicide (Nock et al 2008). Finally, the current sample lacked racial and ethnic diversity, and all participants self selected (and were compensated) to take part in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Depression and mood disorders among adolescents are known predictors of NSSI (Bentley et al, 2015;Duggan et al, 2015;Tuisku et al, 2006), and have also been found in this study. The finding does lend support to the affect regulation theory.…”
Section: Discussionmentioning
confidence: 66%
“…The existing literature has also shown that mental health problems such as anxiety (Claes, Luyckx, Bijttebier et al, 2015), depression (Bentley, Cassiello-Robbins, Vittorio, Sauer-Zavala, & Barlow, 2015;Tuisku et al, 2006), and alcohol and substance use problems (Brausch & Boone, 2015;Gratz & Tull, 2010;Rossow et al, 2007) are significant predictors of NSSI among children and adolescents. Bentley et al (2015) conducted a meta-analysis on 56 studies that examined NSSI among individuals with and without emotional disorders and found that those diagnosed with emotional disorders, such as mood disorders, anxiety disorders, posttraumatic stress disorder (PTSD), and obsessive-compulsive disorder (OCD), were significantly more likely to report engaging in NSSI than their counterparts with no such diagnosis.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Depression is associated with completed or attempted suicide, whether with or without comorbidity (18). In this study, we found that 55.7% of the patients had major depression.…”
Section: Discussionmentioning
confidence: 53%